Social inequalities in self reported health in early old age: follow-up of prospective cohort study - Chandola, Tarani (BMJ Publishing Group Ltd., 2007)
Objective To describe differences in trajectories of self reported health in an ageing cohort according to occupational grade. Design Prospective cohort study of office based British civil servants (1985-2004). Participants 10 308 men and women aged 35-55 at baseline, employed in 20 London civil service departments (the Whitehall II study); follow-up was an average of 18 years. Main outcome measures Physical component and mental component scores on SR-36 measured on five occasions. Results Physical health deteriorated more rapidly with age among men and women from the lower occupational grades. The average gap in physical component scores between a high and low grade civil servant at age 56 was 1.60 and this gap increased by 1 over 20 years. The average physical health of a 70 year old man or woman who was in a high grade position was similar to the physical health of a person from a low grade around eight years younger. In mid-life, this gap was only 4.5 years. Although mental health improved with age, the rate of improvement is slower for men and women in the lower grades. Conclusions Social inequalities in self reported health increase in early old age. People from lower occupational grades age faster in terms of a quicker deterioration in physical health compared with people from higher grades. This widening gap suggests that health inequalities will become an increasingly important public health issue, especially as the population ages.